THE EFFECT OF THE USE OF SEAWEED (Eucheuma cottonii) AS THE SUBSTITUTION MATERIAL TO TAPIOCA FLOUR ON THE QUALITY OF SNAKEHEAD FISH (Channa striata) NUGGET - Rika Yuhalmiana Siregar; Mirna Ilza; Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The study aimed to determine the effect of the use of seaweed (Eucheuma cottonii) as a substitution material to tapioca flour on the quality of snakehead fish (Channa striata) nugget. The method used was experimental method and composed as non-factorial, Completely Randomized Design (RAL). The factor of the treatment was substitution of tapioca flour with seaweed in the processing of snakehead fish nugget, consisting of 4 treatment levels, namely: 75 gs tapioca flour and 0g wet seaweed (N0), 0 g tapioca starch and 75 gs wet seaweed (N1), 50g tapioca flour and wet seaweed 25 gs (N2), 25gs tapioca starch and 50 gs wet seaweed (N3), in each 500 gs of snakehead fish formulation. The results indicated that the snakehead fish nugget substituted by tapioca flour and seaweed showing the significat effect on the value of organoleptic (appearance, odor, taste, texture, folding test), and proximate (water, protein, fiber content) . The quality of snakehead fish nugget using the tapioca starch and seaweed (N2) was showing the highest value of appearance 7.9, aroma 7.1, flavor 7.5, and texture 8.3; as well as the highest value of folding test 5.0 (AA). The content of moisture was 36.64%, protein 12.10%, and crude fiber 1.01%. So that, the best product of snakehead fish nugget proximat with subtitution of 50g tapioca flour and wet seaweed 25 gs (N2) was appropriate to the Indonesia National Standard (SNI 7758-2013).Keywords: Substitution, Seaweed, Nugget, Snakehead Fish